2021
DOI: 10.3390/e23030286
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Entropy: A Potential Digital Marker for Stress

Abstract: Recent decades have witnessed a substantial progress in the utilization of brain activity for the identification of stress digital markers. In particular, the success of entropic measures for this purpose is very appealing, considering (1) their suitability for capturing both linear and non-linear characteristics of brain activity recordings and (2) their direct association with the brain signal variability. These findings rely on external stimuli to induce the brain stress response. On the other hand, researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…These brain rhythms contain relevant information related to mental stress and other psychological disorders. The commonly used spectral EEG features include the power spectral density (PSD), differential asymmetry features, phase synchronization, phase lag index, directed transfer function and entropies [ 29 , 30 , 31 , 32 ]. In addition, the time-frequency features are obtained through the short-time Fourier transform (STFT), or discrete wavelet transform (DWT) [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…These brain rhythms contain relevant information related to mental stress and other psychological disorders. The commonly used spectral EEG features include the power spectral density (PSD), differential asymmetry features, phase synchronization, phase lag index, directed transfer function and entropies [ 29 , 30 , 31 , 32 ]. In addition, the time-frequency features are obtained through the short-time Fourier transform (STFT), or discrete wavelet transform (DWT) [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used EEG to quantify stress states and have found EEG-related markers that can objectively and effectively assess stress ( Peng et al, 2012 ; Minguillon et al, 2016 ; Keshmiri, 2021 ). The present study extended their thoughts to the case of mental fatigue under stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the association between the EEG pattern and stress level [3], [4], [5], [6], [7]. In [8], a combination of time-domain and frequency-domain analysis using wrapper-based algorithms as features and Boruta as feature selector was proposed to identify stress levels using EEG signals.…”
Section: Introductionmentioning
confidence: 99%